Neutralising the effects of branch mismatch arrangements: a South African perspective - Lindeque, Anlia (My University, 2019)
Base erosion and profit shifting (BEPS) has become an increasingly important matter for both multinational enterprises (MNEs) and the countries in which they operate. The tax avoidance strategies used to exploit gaps and mismatches in tax rules have become progressively complex and advanced over the past decade. The aim of this research report is to determine the importance and relevance of addressing BEPS via branch mismatch arrangements, as proposed by the Organisation for Economic Co-operation and Development (OECD), to an emerging economy such as South Africa. The report discusses and analyses the concept of branch mismatch arrangements, the concerns and challenges arising from the use of these arrangements, the recommendations from the OECD in addressing these mismatches and the approaches taken by selected countries. Current domestic legislation is contrasted with international approaches and the recommendations by the OECD. The outcome of adoption or non-adoption of the recommendations will be investigated.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Commerce (specialising in Taxation)
Keywords: UCTD; Base erosion and profit shifting; BEPS; Hybrid mismatch arrangements; Branch mismatch arrangements; Foreign branches; Tax avoidance; International business enterprises--Taxation; Transfer pricing--Law and legislation--South Africa; SDG-8: Decent work and economic growth